Enantiomer specific pharmacokinetics of ibuprofen in preterm neonates with patent ductus arteriosus. Issue 10 (20th April 2020) - Engbers, Aline G.J.; Flint, Robert B.; Völler, Swantje; de Klerk, Johan C.A.; Reiss, Irwin K.M.; Andriessen, Peter; Liem, Kian D.; Degraeuwe, Pieter L.J.; Croubels, Siska; Millecam, Joske; Allegaert, Karel; Simons, Sinno H.P.; et al.
Abstract : Aims: Racemic ibuprofen is widely used for the treatment of preterm neonates with patent ductus arteriosus. Currently used bodyweight‐based dosing guidelines are based on total ibuprofen, while only the S‐enantiomer of ibuprofen is pharmacologically active. We aimed to optimize ibuprofen dosing for preterm neonates of different ages based on an enantiomer‐specific population pharmacokinetic model. Methods: We prospectively collected 210 plasma samples of 67 preterm neonates treated with ibuprofen for patent ductus arteriosus (median gestational age [GA] 26 [range 24–30] weeks, median body weight 0.83 [0.45–1.59] kg, median postnatal age [PNA] 3 [1–12] days), and developed a population pharmacokinetic model for S‐ and R‐ibuprofen. Results: We found that S‐ibuprofen clearance (CLS, 3.98 mL/h [relative standard error RSE 8%]) increases with PNA and GA, with exponents of 2.25 (RSE 6%) and 5.81 (RSE 15%), respectively. Additionally, a 3.11‐fold higher CLS was estimated for preterm neonates born small for GA (RSE 34%). Clearance of R‐ibuprofen was found to be high compared to CLS (18 mL/h [RSE 24%]), resulting in a low contribution of R‐ibuprofen to total ibuprofen exposure. Current body weight was identified as covariate on both volume of distribution of S‐ibuprofen and R‐ibuprofen. Conclusion: S‐ibuprofen clearance shows important maturation, especially with PNA, resulting in an up to 3‐fold increase in CLS during a 3‐day treatment regimen. This rapid increase in clearance needs to be incorporated in dosing guidelines by adjusting the dose for every day after birth to achieve equal ibuprofen exposure.